The Spring Assessing Method of the Threat of Melolontha spp. grubs for Scots Pine Plantations - Hanna Szmidla (Forests, 2019)
Root-feeding Melolonthinae larvae are a forest pest species in Europe that can exert serious damage. In Poland, they are classified as the most dangerous pest on land dedicated to afforestation and the most serious threat to natural regeneration in the stands. This study was performed in three forest districts in east Poland (Lubartów, Marcule, and Wyszków forest districts) in mixed conifer forests, where the presence of Melolontha spp. grubs was evaluated in autumn and spring of 2012 to 2017, respectively. In spring 2012, 2014, and 2016, consecutively ‘small sawdust pits’ in rows between seedlings were prepared, and in adjacent inter-rows similar control pits without sawdust were marked. In spring and autumn of the following year, sawdust and soil from both types of pits were sieved and Melolonthinae larvae were counted and compared. More grubs were found in sawdust pits in spring than in autumn. In Marcule Forest District (FD) (2014), more grubs were found in inter-rows than in rows with seedlings, when compared to grubs detected using the traditional method of “autumn large pits assessment”, recommended by Polish forest rules. The Melolonthinae population size and location of grubs were related to the weather conditions in the evaluated periods, as well. We conclude that to properly assess the cockchafer threat, it is necessary to perform spring assessment and to search in inter-rows. This could be recommended for decisions on control.